Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Perbankan Syariah - Nasfi Nasfi; Rahmad Rahmad; Sabri Sabri (EKONOMIKA SYARIAH : Journal of Economic Studies, 2020)
The object of Islamic banking research of PT. BPRS Hajj Poor Head office of Tanah Land Regency and Payakumbuh City Branch Office, to test the effect of service quality, namely tagible (physical appearance), empathy (attention), reliability (reliability), responsiveness (response) and assurance (guarantee) ) to customer satisfaction. The study population uses accidental sampling (accidental sampling), a sampling technique based on coincidence of savings and financing product customers, which is feasible as a source of data for 10 days, with a sample of 100 people. Analysis of research data on structural equation models, the SPSS application program tests 5 (five) hypotheses that have been developed. 5 (five) hypotheses submitted were accepted, Tangibles had a significant effect on customer satisfaction, tangibles regression coefficient (X1) 0.235 was positive, indicating that with increased tangibles (X1) would increase satisfaction, Empathy had a significant effect on customer satisfaction. Empathy regression coefficient (X2) 0.160 is positive, indicating an increase in empathy (X2) will increase customer satisfaction, reliability has a significant effect on customer satisfaction, reliability regression coefficient (X3) 0.459 customer marks, showing an increase in reliability (X3) increases customer satisfaction, influential responses significant to customer satisfaction. Responsiveness regression coefficient (X4) of 0.787 is positive, indicating increased responsiveness (X4) increases customer satisfaction, Assurance has a significant effect on customer satisfaction, assurance regression coefficient (X5) of 0.514 is positive, shows an increase in Assurance increases customer satisfaction.